Investigation of measurement uncertainties in LNG density and energy for custody transfer. (15th February 2021) - Wu, Thomas Y; Kenbar, Asaad
Abstract: In the custody transfer of fuels such as liquefied natural gas (LNG), energy measurement accuracy is critical. The important elements in calculating transferred energy are the volume, the density and the superior calorific value (SCV). In this paper we have used a new approach to carefully study the various uncertainty factors contributing to two of these elements: the density and the SCV. For density, six methods were evaluated, namely the method of extended corresponding states, the Hiza method, the revised Klosek–McKinley method, the Groupe Européen de Recherche Gazière (GERG-2004) method, the GERG-2008 method, and the equation of state–LNG method, to estimate the modelling error in the density calculation. Other factors affecting LNG density estimation (LNG composition, reference densimeter, temperature and pressure) have also been investigated to derive the total uncertainty in LNG density estimation. For the SCV, the uncertainty has been analysed with consideration given to uncertainties in the composition and the SCV of LNG components. The expanded uncertainty in LNG energy during custody transfer is estimated to be 0.58% ( k = 2) after considering the uncertainties due to the membrane-type tank's unloaded LNG volume, SCV, density and their correlation effect.